Acute and chronic lead exposure and intelligence quotient among Indonesian adolescents: a cross-sectional study - Noviana Dewi; Indah Tri Susilowati (International Journal of Public Health Science (IJPHS), 2026)
Lead exposure is a persistent environmental health concern that can impair cognitive function in adolescents. Therefore, this study aims to examine the association between acute and chronic lead exposure and intelligence quotient (IQ) scores among Indonesian adolescents. A cross-sectional study was carried out involving 39 adolescents who were chosen through purposive sampling. Acute exposure was assessed using blood lead levels(n = 15), while chronic exposure was evaluated with hair lead levels(n = 24). IQ was measured using WAIS administered by a licensed psychologist, while associations between the variables were examined utilizing the Chi-square test. The results revealed that chronic lead exposure was significantly linked to below-average IQ (OR = 1.90; 95% CI: 1.07-3.36), while acute exposure had a weaker relationship (OR = 0.35; 95% CI: 0.13-0.89; p = 0.022). These results indicated the importance of long-term environmental exposure control.